Advanced Surface Engineering Research - Mohammad Asaduzzaman Chowdhury (IntechOpen, 2018)
Surface engineering has rapidly expanded in recent years as the demand for improved materials has increased. Surface engineering is a valuable tool for conceiving both surface and bulk properties, which cannot be achieved simultaneously either by the coating material or by the substrate material alone. The book is written on the current trends of surface engineering and relevant research. The applied and basic research as well as some worthy concepts of materials related to this area is explained clearly to understand the need for surface engineering in industrial applications. The different surface modification processes, properties, and their characterizations are discussed elaborately for future research and as a text book. Modification of surface properties by films or coatings is used in industrial applications. This is an area of interest to numerous fields: fabrication of parts, mechanics, transport, catalysis, energy, production, microelectronics, optoelectronics, the leisure industry, etc. The properties are considered for protection against corrosion, oxidation or wear, biocompatibility, wetting, adhesion, durability, catalytic activity, and toughness. The modern concept of engineering is discussed to ensure that the contributions of this subject minimize energy consumption. The book will be used as a state of the art for present and future researchers, industrial components design, and control.
English
Keywords: Surface Science; Physical Sciences; Engineering and Technology; Materials Science